Kriittinen katsaus rikosoikeuden feministiseen kritiikkiin ja sukupuolispesifiin lainsäädäntöön - Paakkanen, Katariina (Lakimies, 2024)
Lakimies-aikakauskirjan nuorten kirjoittajien palkinto 2024 Critical view on the feminist critique of criminal law and gender-specific criminal legislation The article looks at the feminist critique of criminal law from a point of view of critical legal theory. It uses a few selected examples of gender-based research and legislation to highlight some of the dangers that gendered analysis and gendered criminal law legislation can entail, and that have been to a large part absent from the (feminist) legal discourses. First, it reveals what different definitions of gender feminist critique can entail, and how they can shape the reality they aim to interpret. Next, the article looks at the example of criminal law legislation on female and male genital circumcision/cutting/mutilation, and what issues gender-based legislation causes to criminal law. Gender-based legislation can also create ‘otherness’ by excluding, for example, trans- or non-binary persons from, or forcing them into, its narrow definition of gender. Simultaneously gender-based legislation can conceal ideas of cultural hegemony and reinforce gendered hierarchies that represent men as cultural beings and women as victims of a non-western culture or invisible beings that are outside the scope of western cultural influences. Lastly the article shortly discusses the possibilities of gender-neutral criminal legislation by clarifying the conceptual differences between gender-blind and gender-neutral legislation.